Public Health Management Guidelines of the Cheng Khiri Tambon Peace Council, Sri Sakhon District, Narathiwat Province: The Accessibility of Vaccinations for Children Aged 0-5 Years - กรระสี, ฟาอิก; วงค์ทอง, นภัทร; อะมิยะ, ดาเนียล; บินอิสริส, วันฮารงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to (1) examine and analyze state decentralization through the operational mechanism of the Choeng Khiri Subdistrict Peace Council, Si Sakhon District, Narathiwat Province, using the 4M management framework in the context of improving vaccination access among children aged 0–5 years; and (2) propose a public health management model of the council linked to sustainable decentralization. A qualitative research design was employed. Data were collected through structured in-depth interviews with 18 key informants and analyzed using the 4M framework in conjunction with the Health as a Bridge for Peace (HBP) approach.          The findings indicate that the Choeng Khiri Subdistrict Peace Council has developed an integrated public health management model that effectively enhances vaccination access among children aged 0-5 years. The Manpower and Management dimensions emerged as the primary driving forces through multi-sectoral collaboration among five key sectors. Religious leaders and village health volunteers played critical roles in building community trust, supported using local Malay language communication and trusted community spaces. Financially, the council utilized a multi-source pooled funding approach that increased operational flexibility, although it still lacked full fiscal autonomy. In terms of decentralization, the council functioned as a “practical decentralization mechanism” and an institutional platform enabling participatory and collaborative governance. The HBP framework significantly contributed to transforming health services into a neutral platform for trust-building in a fragile context.